Challenges faced in Latin America for the implementation of an ideal health-care model for rheumatoid arthritis patients: are we ready?. Issue 1 (March 2015) - Jaillier, Juan; Arango, Ana; Pérez, David
Abstract Rheumatoid arthritis (RA) is a chronic, inflammatory, progressive disease characterized by inflammation of the synovial tissue. It results in the severe functional deterioration of the joints involved and the incapacity to work. Our main aim is to determine the characteristics of the current health-care models used in treating rheumatoid arthritis patients in Latin America. We want to analyze the details, using them as the foundation to create an ideal health-care model that is focused on the patient. We have revised documents, including guides to clinical practice, monitoring models and health-care models according to the current policies and resources available in various Latin American countries. Based on this information, the qualities and deficiencies of the current models will be analyzed, in order to use this as a basis on which to construct a proposed health-care model that covers the specific needs of rheumatoid arthritis patients, considering the resources of each population. Despite the collapse seen in many health systems throughout history, we can learn from them and should develop a new model starting from the path pursued, capitalizing on our experiences, teachings, and errors committed. However, in most cases, the obstacles to the success of the systems do not lie in the fundamental structure or the "spirit of the legislator" but rather in the day-to-day development within the community and the special interest of each agent in a system.